The Effectiveness of the Implementation of the Learning Process During the 2019 Coronavirus Disease Pandemic in Ukui District, Pelalawan Regency - Khotami, Khotami; Setiawan, Rizky; Aprilla, Iffa; Andhira, Ayo (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
Since the beginning of 2020, Coronavirus Disease 2019 has spread throughout Indonesia, causing education to change drastically. This caused the learning process in Indonesia to be disrupted, so that for the first time the learning process was carried out online. Ukui District is one of the areas that also implemented online learning during the pandemic. This study aims to determine the effectiveness of the Pelalawan District Education Office in the learning process during the 2019 Coronavirus Disease pandemic in Ukui District. The method used is a qualitative method by collecting data through interviews, observation and documentation. The researcher uses the theory of Dicson and Wetherbe where the results of the research are that the learning process which is carried out online is still considered ineffective due to the lack of ability and skills of education office employees and teachers in using technology, lack of understanding of learning methods that will be applied during the Covid-19 pandemic and equipment inadequate online learning support. The Education Office has tried to make online learning work effectively, but in fact this has not been effective due to existing limitations.